Probability and Random Processes : With Applications to Signal Processing and Communications - Miller, Scott L.; Childers, Donald G. (New Delhi: Elsevier Academic Press, 2011)
Miller and Childers have focused on creating a clear presentation of foundational concepts with specific applications to signal processing and communications, clearly the two areas of most interest to students and instructors in this course. It is aimed at graduate students as well as practicing engineers, and includes unique chapters on narrowband random processes and simulation techniques. The appendices provide a Read more...
Includes index.
Electrical and Electronics Engineering
Keywords: Signal processing -- Mathematics; Probabilities; Stochastic processes